Islamic Guidance and Counseling in the Digital Era: Strategies to Strengthen the Mental Health and Spirituality of the Younger Generation - Amiruddin Z Nur; Arianto; Muh. Samsir Husain; Ulfa Anisyah Agustina; Ali Irbar; Abdul Awal Zikir (EDUJAVARE: International Journal of Educational Research, 2026)
The development of digital technology has brought major changes to communication patterns, social behavior, and the psychological condition of society, particularly the younger generation. Easier access to information and social networks offers considerable benefits, yet it also gives rise to problems such as anxiety, identity crisis, loneliness, digital addiction, and the erosion of spiritual values. This article aims to examine the role and strategies of Islamic guidance and counseling in responding to the mental health and spiritual challenges of young people in the digital era. This study employs a qualitative approach using the library research method on classical and contemporary literature relevant to Islamic guidance and counseling, Islamic psychology, and digital social phenomena. The findings show that Islamic guidance and counseling remain highly relevant through the integration of Qur'anic and Hadith values with modern counseling approaches, the utilization of digital media as a da'wah medium, character strengthening, and synergy among families, educational institutions, and religious counselors. This article is expected to serve as both an academic and practical reference for counselors, religious counselors, and Islamic educators in designing guidance models that are adaptive to the times.